Cultura de los Comerciantes del Municipio de Unión Panamericana en la Contribución del Impuesto de Industria y Comercio (2020)
This study will analyze the incidence of the factors that have been influencing the behavior of the tax collection, with the sole objective of contributing to new elements that improve the municipal taxation. This project will study the culture of nonpayment of the Industry and Commerce tax in the municipality of Union Panamericana, which in turn will provide an analysis that will encourage the tax culture in relation to the Industry and Commerce tax. Providing data and recommendations to attack the main causes of the culture of nonpayment of the industry and trade tax by the Pan American Union traders; likewise, it is important to determine: the economic and social impact generated by the evasion of the industry and tradetax.